2005
DOI: 10.1038/sj.npp.1300766
|View full text |Cite
|
Sign up to set email alerts
|

Increased Pituitary Volume in Antipsychotic-Free and Antipsychotic-Treated Patients of the Æsop First-Onset Psychosis Study

Abstract: Subjects at their first psychotic episode show an enlarged volume of the pituitary gland, but whether this is due to hypothalamicpituitary-adrenal (HPA) axis hyperactivity, or to stimulation of the prolactin-secreting cells by antipsychotic treatment, is unclear. We measured pituitary volume, using 1.5-mm, coronal, 1.5 T, high-resolution MRI images, in 78 patients at the first psychotic episode and 78 age-and gender-matched healthy controls. In all, 18 patients were antipsychotic-free (12 of these were antipsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
83
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(100 citation statements)
references
References 60 publications
12
83
5
Order By: Relevance
“…In contrast, their simultaneous clustering over time in those exposed to prolactin-sparing medications suggests an underlying common and central vulnerability, involving more than one central dopamine tract, that may be intrinsic to schizophrenia itself, and only detectable in the absence of external agents causing substantial increases in plasma prolactin that overshadow this internal, illness-related, association. Indeed, a recent investigation reported pituitary enlargement in nevermedicated patients with schizophrenia, compatible with the hypothesis of a central, illness-related, mechanism (Pariante et al, 2005). Similarly, a recent report found high prolactin levels in a paranoid subgroup of never-medicated psychotic patients, suggestive of the existence of subtypes of psychotic illness associated with differences in dopaminergic tone (Segal et al, 2004).…”
Section: Discussionmentioning
confidence: 60%
“…In contrast, their simultaneous clustering over time in those exposed to prolactin-sparing medications suggests an underlying common and central vulnerability, involving more than one central dopamine tract, that may be intrinsic to schizophrenia itself, and only detectable in the absence of external agents causing substantial increases in plasma prolactin that overshadow this internal, illness-related, association. Indeed, a recent investigation reported pituitary enlargement in nevermedicated patients with schizophrenia, compatible with the hypothesis of a central, illness-related, mechanism (Pariante et al, 2005). Similarly, a recent report found high prolactin levels in a paranoid subgroup of never-medicated psychotic patients, suggestive of the existence of subtypes of psychotic illness associated with differences in dopaminergic tone (Segal et al, 2004).…”
Section: Discussionmentioning
confidence: 60%
“…higher diurnal cortisol levels and greater blunting of the CAR) were associated with poorer memory and executive function, possibly reflecting underlying dysfunction in the brain regions which mediate both HPA axis function and these cognitive functions [43]. Neither ASz nor FHx children were characterised by pituitary volume enlargements [35], which contrasts with those identified among individuals with firstepisode psychosis [66][67][68][69] and in some (but not all) studies of older individuals at-risk for psychosis [69,70]. Among FHx children only, pituitary volume was negatively associated with current distress relating to negative life events and exposure to physical punishment [35], implying that psychosocial stressors may contribute to pituitary volume changes among those with family history.…”
Section: Hypothalamic-pituitary-adrenal (Hpa) Axis Dysfunctioncontrasting
confidence: 40%
“…Animal studies have shown that circulating glucocorticoids play a permissive role in inducing the host immune response and behavioral changes such as increased locomotion and aggression. 24 Interestingly, several studies have reported elevated cortisol levels, increased production of interleukin-2 (IL-2) and IL-6 45,46 and increased volume of the pituitary gland 47,48 in schizophrenia patients compared to healthy controls. IL6 has been shown to stimulate the hypothalamicpituitary axis 46 thus possibly setting up a vicious circle that may confer vulnerability to brain structural alterations in schizophrenia patients but not in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%